Technical challenge in MCA bifurcation aneurysm clipping - Nepal, Pankaj Raj (Eastern Green Neurosurgery, 2019)
Technical challenges in aneurysms can broadly be divided into general aneurysmal management challenges and aneurysm specific challenges. Specifically, we usually prefer to select the approach based on the presence or absence of temporal hematoma, and the length of the M1 segment. In the presence of temporal lobe hematoma it is wise to select the superior temporal gyrus approach, as hematoma evacuation is easy and we usually find the M3 segment to trace back to find the aneurysm. Other challenge lies while clipping the aneurysm. MCA bifurcation aneurysm seems to be the most notorious type, because of its varied morphology. We may find them a simple, multiple lobed, giant, fusiform, and occasionally its the M2 stuck to the neck of the aneurysm or arising from its dome. For multiple lobed MCA bifurcation aneurysm, the pearls of clipping is to think different lobes as a different aneurysms.